Analisis Kemampuan Berfikir Kreatif Siswa pada Pembelajaran Biologi Ditinjau dari Prestasi Siswa Kelas VIIIA Di Sekolah Menengah Pertama (SMP) Negeri 12 Sungai Penuh - Seprianto Seprianto (Institut Agama Islam Negeri Kerinci, 2021)
The purpose of this study was to determine the creative thinking ability of students who are high achievers, medium achievers, low achievers at SMP Negeri 12 Sungai Penuh and to determine a comparative analysis of the creative thinking abilities of all students in biology learning at SMP Negeri 12 Sungai Penuh. This type of research is descriptive qualitative research. informants in the study were biology teachers and students at SMP Negeri 12 Sungai Penuh. The data collection techniques used were observation, interview and documentation methods. The results of the research are the creative thinking abilities of high achieving students are students who have the maximum creative thinking stage, Students who have high creative thinking abilities have better achievement and their thinking abilities follow the stages in creative thinking skills. are students who have the ability at several stages of creative thinking, but there are also some stages of creative thinking that still cannot be implemented properly and optimally. Such as the illumination stage and the verification stage. Students with low creative thinking abilities have low learning achievement. The stages carried out are still very poor at the preparation, incubation, illumination and verification stages. Keywords: Creative Thinking, Achievement